Diagnosis Molekuler Human Papilloma Virus (HPV) Penyebab Kanker Serviks - Lipinwati . (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Cervical cancer is still the one of major public health problem in the world whether an effective screening programs using the Papanicolaou test to detect precancerous lesions has reduced the number of cases of cervical cancer in the developed countries but not in developing countries. The sensitivity and specificity of the Pap smear depends on observer’s skills to recognize and classify variations of abnormal cells. Human Papilloma Virus (HPV) caused cervical cancer has been proved, In some study have found HPV DNA in 99.7 % of all cervical carcinomas. HPV has been found to be more than 100 genotypes , which are divided into high-risk HPV and low-risk HPV The development of early diagnosis for the detection of HPV infection still has been a problem, where the cytology and colposcopy to identify lesions at an advanced stage, therefore the molecular engineering approach seems to be more successful in early diagnosing cervical cancer. This technique of molecular HPV DNA sequences are Southern Blot Hybridization, Hybrid Capture II Assay, Polymerase Chain Reaction, and PCR - Reverse Line Blot. The Accuracy of molecular diagnostic techniques is required to provide further information for patient how the management and maintenance of cervical cancer. Keywords: Cervical cancer, HPV, screening, molecular techniques